The Extended Amygdala and the Dopamine System: Another Piece of the Dopamine Puzzle - Fudge, Julie L. (2003)
The dopamine system (DA) has long been associated with the pathophysiology of psychosis. The DA theory of schizophrenia continues to find support in neuroreceptor imaging and ligand-binding studies that show excess DA transmission in patients, as compared to controls. The pathways which regulate the primate DA system, however, have yet to be fully elucidated. The amygdala, including its extended amygdala component, is involved in evaluating the emotional value of sensory stimuli. Since emotionally relevant sensory stimuli are distorted during psychotic episodes, we hypothesize that amygdaloid influences are likely to be significant modulators of the DA system. We reviewed evidence for direct projections from the central extended amygdala to specific subpopulations of DA neurons, and we discussed how these pathways may serve as important conduits of emotionally relevant information that can have immediate and long-term effects on DA regulation.